Integrating Video Storytelling Strategies in Recent Curriculum Implementation to Enhance Social Media Audience Engagement - Aswadi Jaya; Sherli Triandari; Fhia Amelia; Ramzi Zainum Ikhsan; Ariana Delhi; Nuke Puji Lestari Santoso (Pandawan, 2026)
The rapid growth of social media has transformed digital communication practices and influenced recent curriculum implementation in digital learning and communication studies. Video-based content has become an important medium for delivering educational and promotional messages because it combines visual, audio, and narrative elements that enhance audience attention and emotional engagement. However, the increasing volume of social media content creates intense competition, requiring adaptive communication strategies to improve interaction effectiveness. One widely applied approach is video storytelling, which delivers messages through structured and meaningful visual narratives. This study aims to analyze the integration of video storytelling strategies in recent curriculum implementation to enhance social media audience engagement, measured through indicators such as likes, comments, shares, and watch duration. This research applies a descriptive qualitative method supported by engagement analytics through observation of video storytelling content, documentation of interaction metrics, and literature review. This study proposes a platform-adaptive storytelling framework that explains differences in engagement patterns across TikTok, Instagram, and YouTube by emphasizing narrative structure, emotional engagement, and platform suitability. The findings show that concise storytelling, emotional appeal, visual consistency, and alignment with platform characteristics significantly influence audience interaction and retention. The study concludes that integrating video storytelling strategies into recent curriculum implementation provides an effective digital communication approach for improving audience engagement and supporting adaptive learning and communication practices in contemporary social media environments.